THE ROLE OF MODERN PEDAGOGICAL TECHNOLOGIES IN ENHANCING EDUCATIONAL EFFECTIVENESS (Prima Journal of Integrated Studies, 2026)
This article analyzes the role and significance of modern pedagogical technologies in the educational process. In particular, digital platforms, AI-based adaptive systems, virtual and augmented reality (VR/AR), gamification, and blended and flipped classroom models are examined in terms of their impact on developing students’ critical thinking, problem-solving skills, and individualized learning. The paper also discusses challenges associated with implementing these technologies and suggests possible solutions.
Keywords: Pedagogical technology, innovative approaches, digital education, artificial intelligence, VR/AR, gamification, flipped classroom, educational effectiveness.